Methods and devices for treating pruritus - WANG TIANXIN (2024)
The present invention describes non-invasive methods and devices for improving health, such as the treatment of pruritus, especially skin pruritus. The non-invasive means are selected from electrical stimulation, hot or cold stimulation, IR (Infrared) radiation, mechanical stimulation, or a combination thereof. In some embodiments, the methods and devices utilize current flow through the skin of a site having an itch feeling to achieve desired treatment and benefits. 本发明描述了用于改善健康例如治疗瘙痒尤其是皮肤瘙痒的非侵入性方法和装置。非侵入性手段选自电刺激、热或冷刺激、IR(红外)辐射、机械刺激或其组合。在一些实施例中，该方法和装置利用经过具有发痒感的部位的皮肤的电流来实现期望的治疗和有益效果。